(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the features of a systematic approach to the organization and structuring of the consultative and therapeutic process. The authors present the System Integrative Model of Psychotherapy and Counseling (SIMPC). The article details the features of each stage of work within the framework of the proposed model: precontact; first meeting; research; design and conceptualization; changes and development; stabilization; completion and postcontact. The authors offer a comprehensive multi-module author’s program “System Integrative Counseling and Psychotherapy”, which is aimed at training a system non-medical psychotherapist and consultant. It is designed for psychologists and other s pecialists o f the helping professions. The program determines the content and structure of classes, has a practical orientation and contributes to the formation of a professional holistic identity of a specialist.